A Grand Battle between the Irish Hen and the English Bantam. - (:unkn) unknown (Holland, William, 1799)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Ireland -- History -- Union, 1801; Ireland ? Relations ? Great Britain; Irish -- Caricatures and cartoons; British -- Caricatures and cartoons; Scots -- Caricatures and cartoons